Review on Chinese and International Research About Transition to School - Shujing Cui (Karolinum Press, 2023)
Transition to school lays the foundation for development of children throughout the school year. It is a research topic of interest across many countries including China. Extant reviews on transition to school mainly addressed international research written in English, however, the major foci and research findings of Chinese research were not included. This review included 131 international studies and 113 Chinese studies on school readiness and transition to school, from 1999 to 2021, to identify major foci and findings of both international and Chinese research on this topic. A considerable of overlap of foci and consistent findings between international and Chinese transition research were found in this review. The unique focus of Chinese research on psychological pressure of children in transition to school and its implication were discussed. Differences of methods adopted in international and Chinese studies were identified. Conclusions about the trends and future research directions are presented.